Preparation and characterization of Li-Zn-Barium ferrite nano powder for bio applications - Ali, Saffa’a Hussein; Abbas, Zena Mohammed Ali (Edelweiss Applied Science and Technology, 2025)
Substituted barium hexaferrite, represented as BaFe12−2xLixZnxO19 (where x values are 0.2, 0.4, 0.6, and 0.8), was synthesized using the auto-combustion sol-gel technique. This research examined the structural features and magnetic properties of barium ferrite with varying quantities of non-magnetic replacements (Zn²⁺ and Li⁺ ions) via various analytical methods. The processed XRD powder patterns confirmed the existence of a single-phase structure, indicating that both Zn²⁺ and Li⁺ ions successfully integrated into the barium hexaferrite lattice without disrupting its hexagonal structure. FTIR spectra displayed prominent bands associated with barium hexaferrite and hydroxyl (OH) groups. The EDS results confirmed the successful incorporation of the non-magnetic cations into the structure. FESEM images showed that all samples exhibited a hexagonal phase, and as the substitution of cations in the barium ferrite structure increased, the particle size decreased. Furthermore, with an increasing x value, the grains tended to elongate into rod-like shapes. The saturation magnetization (Ms) and remanent magnetization (Mr) both decreased, reaching minimum values of 5.462 emu/g and 7.08 emu/g, respectively. In contrast, the coercive field (Hc) increased significantly, particularly at x = 0.4, where it reached a maximum value of 4358 Oe. The squareness ratio (Mr/Ms), which exceeded the theoretical value of 0.5, confirmed that the hexaferrite powders demonstrated strong uniaxial anisotropy.